2003
DOI: 10.1136/jme.29.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Relatives' attitudes towards informing patients about the diagnosis of Alzheimer’s disease

Abstract: Objectives: To evaluate relatives' attitudes towards informing patients with Alzheimer's disease (AD) about their diagnosis. Setting: A university hospital in Italy. Methods: The closest relatives of each of 71 subjects diagnosed for the first time as having AD were interviewed, using a semistructured questionnaire. Spontaneous requests by relatives not to communicate issues concerning the diagnosis were also recorded. Results: Forty three (60.6%) relatives spontaneously requested that patients not be fully in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 19 publications
(9 reference statements)
0
34
0
1
Order By: Relevance
“…Nevertheless, most of the people interviewed in this study would want their own diagnosis revealed to them should they suffer from AD. This somewhat conflicting aspect, had already been noted in studies carried out in Italy 17 and Ireland…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, most of the people interviewed in this study would want their own diagnosis revealed to them should they suffer from AD. This somewhat conflicting aspect, had already been noted in studies carried out in Italy 17 and Ireland…”
mentioning
confidence: 88%
“…Forty three (60.6%) relatives spontaneously declared their wish for patients not to be informed of the diagnosis. Following the interview, all interviewees felt the patient should not be told of the diagnosis, fearing bringing on or worsening depressive symptoms for the patients 17 . This result is similar to that found in Ireland by Conor et al, showing that this fear of the emotional impact on the patient following disease diagnosis disclosure is prevalent among patient relatives 14 .…”
mentioning
confidence: 99%
“…This was done because some people may have been unaware of their own diagnosis. A study in Italy reported how a number of carers asked for their relatives not to be fully informed of their Alzheimer's (Pucci et al, 2003). Although there is no evidence to suggest that diagnoses of these neurological conditions are concealed from those with it, there may have been cases where people knew their condition by a different name, but may have recognised the symptoms.…”
Section: Mediamentioning
confidence: 99%
“…The finding of the latter study is congruent with that by Puce and colleagues involving 71 closest relatives of patients diagnosed with Alzheimer's disease for the first time who were interviewed. They reported that 60.6% were not in favour of their loved one being fully informed that they had Alzheimer's disease [21]. The justifications of this position by relatives include their own emotional difficulty in accepting and coping with the psychological reaction of their loved one and the risk of onset and possible worsening symptoms of depression in the patient [21].…”
Section: Attitudementioning
confidence: 99%